Evaluasi Penerapan Pembiayaan Mudharabah Dan Pengaruhnya Terhadap Laba Perusahaan Studi Kasus pada PT Bank Muamalat Indonesia Tbk, Cabang Bogor - Rosita, Siti Ita; Rahman, Abdul (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2011)
Mudharabah financing is an agreement of cooperation between the banking business as the owner of the funds (Shahibul maal) and the customer as the fund manager (mudharib) to do business with revenue sharing (profit or loss) by agreement in advance. The purpose of this study was to evaluate the implementation of financing and the impact on corporate earnings in a sharia banks. The evaluation was done to determine how the application of financing is done in Islamic banks have an effect on company profits. Research carried out writer in PT Bank Muamalat Indonesia Tbk Bogor branch located at Jalan Bantar Jati Pajajaran No. 105 â Bogor. The results of this study indicate that financing is in PT Bank Muamalat Indonesia Tbk Bogor Branch provided in the form of working capital in the form of cash and noncash assets. The amount of revenue sharing at the beginning of financing is determined in accordance with agreement between both parties, and in determining the amount of revenue sharing method. The evaluations in this study show PT Bank Muamalat Indonesia Tbk Bogor Branch has adopted of financing in accordance with accounting guidelines Indonesian Islamic Banking and Indonesia Standard of Financial Accounting Statement No. 105. In relation to income, financing is contributing to an increase or decrease in earnings of PT Bank Muamalat Indonesia Tbk Bogor Branch. Based on the financial statements of the Bank Muamalat Indonesia in 2008-2007, it is known that the financing mudharabah substantial contribution to the improved earnings PT Bank Muamalat Indonesia Tbk Bogor Branch.